Accuracy Assessment of Relative GPS as a Function of Distance and Duration for CORS Network - Gond A.K.; Ohri A.; Maurya S.P.; Gaur S. (My University, 2025)
Indian mapping agency, Survey of India (SOI), is ambitiously implementing nation-wide network of Continuously Operating Reference Stations (CORS) to improve the accuracy of derived three-dimensional relative positions of the Global Navigational Satellite System (GNSS) over the regions. However, it does not only improve the accuracy but also reduce the cost of reliable data acquisition. Recently, SOI has established a number of CORS networks and continues to cover the entire India for its suitability in the infrastructure projects and in the generation and updating of revenue maps. The present article attempts to measure the accuracy of a single baseline static survey carried out using the CORS network by studying fifteen stations established in different parts of Uttar Pradesh and Madhya Pradesh. To study the accuracy using the established CORS network, 7 days of continuous observed data from fifteen stations of Uttar Pradesh and Madhya Pradesh have been processed. The study has been done taking a base–rover combination with varying distance (D) from 30 to 160 km and the time duration (T) at 20 min, 1 h, 2 h, 4 h, 8 h, 12 h, and 24 h using observational CORS data (including both GPS and GLONASS). The present study shows that (i) dependence of accuracy on distance (D) up to 160 km is almost negligible when final ephemeris data of GPS satellite orbit (International GPS Service) have been used and (ii) the positional accuracy improved with an increase in observation duration. Finally, regression analysis has been done to establish the relationship between distance (D), duration (T), and accuracy for the given CORS network. © 2023, Indian Society of Remote Sensing.